Positive Solution to a Fractional Boundary Value Problem. (11th August 2011) - Guezane-Lakoud, A.; Khaldi, R.
Abstract : A fractional boundary value problem is considered. By means of Banach contraction principle, Leray-Schauder nonlinear alternative, properties of the Green function, and Guo-Krasnosel'skii fixed point theorem on cone, some results on the existence, uniqueness, and positivity of solutions are obtained.